Detection of neutrophil extracellular traps in patient plasma: method development and validation in systemic lupus erythematosus and healthy donors that carry IRF5 genetic risk - Matta, Bharati; Battaglia, Jenna; Barnes, Betsy J. (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) are web-like structures extruded by neutrophils after activation or in response to microorganisms. These extracellular structures are decondensed chromatin fibers loaded with antimicrobial granular proteins, peptides, and enzymes. NETs clear microorganisms, thus keeping a check on infections at an early stage, but if dysregulated, may be self-destructive to the body. Indeed, NETs have been associated with autoimmune diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), antiphospholipid syndrome (APS), psoriasis, and gout. More recently, increased NETs associate with COVID-19 disease severity. While there are rigorous and reliable methods to quantify NETs from neutrophils via flow cytometry and immunofluorescence, the accurate quantification of NETs in patient plasma or serum remains a challenge. Here, we developed new methodologies for the quantification of NETs in patient plasma using multiplex ELISA and immunofluorescence methodology. Plasma from patients with SLE, non-genotyped healthy controls, and genotyped healthy controls that carry either the homozygous risk or non-risk IRF5-SLE haplotype were used in this study. The multiplex ELISA using antibodies detecting myeloperoxidase (MPO), citrullinated histone H3 (CitH3) and DNA provided reliable detection of NETs in plasma samples from SLE patients and healthy donors that carry IRF5 genetic risk. An immunofluorescence smear assay that utilizes only 1 µl of patient plasma provided similar results and data correlate to multiplex ELISA findings. The immunofluorescence smear assay is a relatively simple, inexpensive, and quantifiable method of NET detection for small volumes of patient sera.